(untitled) (Journal of Laboratory Animal Science, 2024)
The objective of this study was to compare changes in leucocyte and lymphocyte analytes in various models of immunodeficient mice lacking T or B or NK cells or both T and B cells. In this study, we used the following immunodeficient mice (nu; T inactive B+ NK+), (IgH-6-/-; T+B inactive NK+) (beige; T+B+NK inactive) and SCID and RAG-1-/- (T inactive B inactive NK+). Among the T cell deficient (Ii-/-, CD8+, CD4 Inactive) and (TAP-1-/-; CD 4 inactive and CD8+) were used. FACS analyses of peripheral-blood mononuclear cells were performed to determine the percentage of CD3+ T cell, B220 + B cell and NK cell along with analysis of hematological parameters. There were marked differences in the relative proportions of leucocytes and lymphocytes blood cell population among the immunodeficient strains. These results indicate that WBC and lymphocytes population in whole blood depends on T cells percentage. B cells and NK cells deficiency has minor role in the leucocytes and lymphocytes population in immunodeficient status in mouse models. The hematological differences described here are based on the level of CD3, B220 and NK1.1 cells. This study will provide baseline information for researchers who use various immunodeficient mice for immunological, genetic and cancer studies.